Clinical and economic impacts of optical coherence tomography prior to cataract surgery in a low-to-middle-income country - Inkarbekov, Mansur; Kulmaganbetov, Mukhit; Bazarbekova, Galiya; Baiyrkhanova, Almagul; Thompson, Benjamin (Frontiers in Ophthalmology, 2026)
BackgroundIntegrating optical coherence tomography (OCT) into the pre-surgical stage of cataract management holds significant clinical and economic potential, particularly in low-to-middle-income countries like Kazakhstan.ObjectiveThis study aimed to evaluate these impacts by prospectively recruiting 225 patients, aged 71 ± 6 years, from two ophthalmology surgical centers in Almaty, Kazakhstan.MethodsPatients undergoing phacoemulsification of cataracts with monofocal intraocular lens (IOL) implantation between January 2022 and December 2023 were divided into two groups: the OCT group (n=75) received pre-operative OCT, while the Control group (n=150) did not. Visual acuity (VA) was measured pre- and post-surgery, and the cost-effectiveness of the surgical strategies was analyzed.ResultsThe OCT group experienced a significantly greater improvement in VA (-0.647 ± 0.232 logMAR) compared to the Control group (-0.543 ± 0.244 logMAR), with a notable interaction between time and group (F(df) = 396.5, p< 0.001). Additionally, pre-existing concomitant diseases were diagnosed in 24.8% of cases in the OCT group and 31% in the Control group.ConclusionThe economic analysis revealed that the integration of OCT facilitated combined surgical procedures during a single operative session, thereby reducing overall costs. These findings suggest that implementing OCT in the pre-surgical stage of cataract management can significantly enhance visual outcomes and decrease the cost of ophthalmology services in Kazakhstan.